SHORT SOFT Г-RAY BURST SPECTRAL EVOLUTION - Kondratyev, V. N. (Одеські астрономічні публікації, 2017)
Short Soft Gamma-Ray bursts are considered as neutron star crust magnetoemission. Statistics of temporal burst properties are shown to display univesal features.